Comprehensive Physiology 2019
DOI: 10.1002/cphy.c180008
|View full text |Cite
|
Sign up to set email alerts
|

Muscles of Breathing: Development, Function, and Patterns of Activation

Abstract: This review is a comprehensive description of all muscles that assist lung inflation or deflation in any way. The developmental origin, anatomical orientation, mechanical action, innervation, and pattern of activation are described for each respiratory muscle fulfilling this broad definition. In addition, the circumstances in which each muscle is called upon to assist ventilation are discussed. The number of “respiratory” muscles is large, and the coordination of respiratory muscles with “nonrespiratory” muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
32

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 447 publications
0
12
0
32
Order By: Relevance
“…Similarly, a study by Rehan et al found that thickness of the diaphragm, another abdominal muscle, was positively correlated with PMA at measurement and infant weight and length but not nutrition intake (calories) 19 . Respiration during oral feeding in preterm infants involves both effective inspiration and expiration; the diaphragm is primarily involved in the inspiration phase of the respiratory cycle, whereas the rectus abdominis is involved in both expiration and early inspiration 20,21 . The coordination and rhythm of respiration to swallow is a complex process that requires the infant to have a paucity of respiration to allow for swallow (deglutition) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Rehan et al found that thickness of the diaphragm, another abdominal muscle, was positively correlated with PMA at measurement and infant weight and length but not nutrition intake (calories) 19 . Respiration during oral feeding in preterm infants involves both effective inspiration and expiration; the diaphragm is primarily involved in the inspiration phase of the respiratory cycle, whereas the rectus abdominis is involved in both expiration and early inspiration 20,21 . The coordination and rhythm of respiration to swallow is a complex process that requires the infant to have a paucity of respiration to allow for swallow (deglutition) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In the same process of stretching, skeletal muscles may play a more critical role, because they provide the force required for the process of mouth breathing (Pilarski et al, 2019). Through trichrome staining, we found that the skeletal muscles undergo significant alteration in the proliferation of collagen due to the stretching effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients who suffer from TMD always have sleep‐apnea‐related problem, while patients who complain about sleep disorders tend to be at risks from TMD (Sanders et al., 2013; Yamada, Tanne, Miyamoto, & Yamauchi, 1997). Considering that hypoxia and mouth breathing are the two main clinical manifestations of pediatric OSA, and that their impacts and outcomes are not yet fully understood, it becomes imperative to determine the mechanisms and effects of hypoxia and mouth breathing on early facial development (Huang & Guilleminault, 2017; Sato et al., 2018; Pilarski et al, 2019). This is the case particularly because if mouth breathing, rather than hypoxia, plays a greater role in affecting the development of the TMJ in children, then these children need to receive treatment as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Extrinsic muscle contraction can protrude or retract the tongue as well as depress the tongue base. Table 1 summarizes the innervation and mechanical actions of the tongue muscles based on prior publications [7][8][9][10].…”
Section: Tongue Muscles and Motoneuronsmentioning
confidence: 99%